Finite‐element modeling of the seismic response of reinforced masonry wall structures. (18th November 2020) - Koutras, Andreas A.; Shing, P. Benson
Abstract: Modern design codes and performance‐based earthquake engineering rely heavily on computational tools to assess the seismic performance and collapse potential of structural systems. This paper presents a detailed finite‐element (FE) modeling scheme for the simulation of the seismic response of reinforced masonry (RM) wall structures. Smeared‐crack shell elements are combined with cohesive discrete‐crack interface elements to capture crushing and tensile fracture of masonry. Beam elements incorporating geometric as well as material nonlinearity are used to capture the yielding, buckling, and fracture of the reinforcing bars. The beam elements are connected to the shell elements through interface elements that simulate the bond‐slip and dowel‐action effects. An element removal scheme is introduced to enhance the robustness and accuracy of the numerical computation. The material models and interface elements have been implemented in a commercial FE analysis program. The modeling scheme is validated with data from quasi‐static cyclic tests on RM walls as well as with results from shake‐table tests on RM building systems.